Analisis Kesalahan Penggunaan Fukujoshi Mo, Sae dan Made pada Mahasiswa Pembelajar Bunpou 6 Tahun Ajaran 2010/2012 Jurusan Bahasa Jepang Fakultas Bahasa dan Seni Universitas Negeri Jakarta (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2012)
By beginning research, researcher know that the learners find difficulty of the usage of fukujoshi mo, sae, and made that have similar function and sometimes can replace each other. It causes error of the usage. By descriptive method this research is done for getting information about the error level of the usage of fukujoshi mo, sae, and made, that error type, and the cause of that error.